Improving barrier and antibacterial properties of chitosan composite films by incorporating lignin nanoparticles and acylated soy protein isolate nanogel. (January 2023) - Zou, Zhipeng; Ismail, Balarabe B.; Zhang, Xinhui; Yang, Zhehao; Liu, Donghong; Guo, Mingming
Abstract: Chitosan (CS) films have demonstrated strong antibacterial properties, excellent biocompatibility and biodegradability, but poor UV blocking, oxygen and water barrier and mechanical properties limit their application in antimicrobial food packaging. In this study, CS films were incorporated with nanofillers, including lignin nanoparticles (LNP, 1–5 wt %) and acylated soy protein isolate nanogel (ASPNG, 3–7 wt %) to improve their tensile strength, oxygen and water barrier, UV blocking and antibacterial properties. SEM images illustrated that the addition of LNP and ASPNG significantly affected the surface morphology of the CS film. Meanwhile, LNP incorporation improved UV blocking property of composite film, while an improved sustained antibacterial property was achieved with ASPNG incorporation. Interestingly, CS composite film incorporated with 3% LNP and 5% ASPNG showed a remarkable increase in tensile strength (37.29–54.29 MPa) and decreased oxygen barrier property (5.73–2.83 cm 3 /m 2 ·24 h MPa) relative to pure CS film. It is worth mentioning that the bacterial counts in samples treated by 3% LNP/5% ASPNG-CS composite film decreased approximately 2.37 log CFU/mL, which exhibited higher antibacterial activity than other composite films. However, this study also demonstrated that incorporation of LNP and ASPNG slightly decreased the light transmission and increased surface roughness of CS film. All in all, the CS composite film with enhanced mechanical, barriers, antibacterial properties were obtained by incorporating an appropriate proportion of LNP and ASPNG and could further be utilized as a promising antibacterial food packaging material. Graphical abstract: Image 1 Highlights: Lignin nanoparticles (LNP) and acylated soy protein isolate nanogel (ASPNG) were fabricated. LNP and ASPNG incorporation improved tensile strength and elongation at break of the film. LNP and ASPNG incorporation improved oxygen and water vapor barrier properties of the film. 3% LNP/5% ASPNG enhanced CS film's potassium sorbate sustained release ability. 3% LNP/5% ASPNG-CS film had higher antibacterial activity than pure chitosan film.